if f(x)=(3x-27)/14 then find f(f^-1(241))
f(x) = (3x - 27)/14
the inverse of our function f^-1(241) = 14/(3x - 27)
= 14/(3*241-27) = 0.0201
then f(f^-1(241)) = f(0.0201) = (3(0.0201) - 27)/14 = -1.92
actually the correct answer is 241 itself because it must start and end the same
please allow me to correct it. thank you
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?